2001
DOI: 10.1038/sj/ijo/0801906
|View full text |Cite
|
Sign up to set email alerts
|

Brain reward circuitry and the regulation of energy balance

Abstract: Reward signals contribute to the regulation of energy balance by influencing switching between feeding and competing behaviors. Properties of natural rewards are mimicked by electrical stimulation of certain brain regions. The rewarding effect produced by stimulating the perifornical region of the hypothalamus is modulated by body weight and is attenuated both by leptin and insulin. Research is reviewed concerning the dependence of the rewarding effect of perifornical stimulation on longterm energy stores and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…An fiϩ action of leptin may be consistent with the data of Shizgal and colleagues (10,33), who found that electrical stimulation of lateral hypothalamic neural networks in rats increases sucrose ingestion, which can either be attenuated or augmented by intracerebroventricular leptin administration, depending on the location of the electrical probe. Thus, depending on the activity of neuronal networks in the lateral hypothalamus, leptin may either have orexigenic or anorexigenic effects.…”
Section: R759supporting
confidence: 73%
“…An fiϩ action of leptin may be consistent with the data of Shizgal and colleagues (10,33), who found that electrical stimulation of lateral hypothalamic neural networks in rats increases sucrose ingestion, which can either be attenuated or augmented by intracerebroventricular leptin administration, depending on the location of the electrical probe. Thus, depending on the activity of neuronal networks in the lateral hypothalamus, leptin may either have orexigenic or anorexigenic effects.…”
Section: R759supporting
confidence: 73%
“…It is also useful to teasing apart whether dopamine and related limbic systems code reward learning vs incentive salience by pitting dopamine's influence on dynamically shifted motivation values against more stable learned reward values (V) (see below). Dopamine is important to dynamic modulation because it is a crucial component of the mesocorticolimbic circuitry that mediates the integration of learned signals with hunger/ satiety states to dynamically transform the motivational value of stimuli (Ahn and Phillips 1999;Fiorino et al 1997;Fulton et al 2000;Laviolette et al 2002;Nader et al 1997;Shizgal 1999;Shizgal et al 2001;Wilson et al 1995). Neural mechanisms for that integration involve inputs from other brain systems, such as hypothalamic orexin and other signals about physiological homeostasis, that impact on mesolimbic function (Baldo et al 2003;Harris et al 2005;Kelley et al 2005a;Narita et al 2006;Zheng et al 2003).…”
Section: Stages Involved In Attributing Incentive Saliencementioning
confidence: 99%
“…Leptin regulates the perception of the rewarding value of palatable food (as well as that of other addictive substances, such as drugs of abuse) (112)(113)(114)(115).…”
Section: Other Potential Mechanisms Of Leptin Resistancementioning
confidence: 99%